PENGARUH KOMPETENSI, QUALITY OF WORK LIFE DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI - Jasib Jasib; Nurwati Nurwati; Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to examine and analyze the effect of competencies, quality of work life and workload on employee job satisfaction in the ministry of the city / land office of the city of Southeast Sulawesi Province. This research is a quantitative approach. The population in this study were employees in the ministry of the city / municipal land office of the city of Southeast Sulawesi with a sample of employees of 42 people. The analysis used multiple regression analysis with the help of IBM MSS software 22. The results showed that (1) competence, quality of work life and workload had a positive and significant effect on employee job satisfaction, (2) competence had a positive and significant effect on employee job satisfaction, (3) quality of word life has a positive and significant effect on employee job satisfaction, and (4) workload has a positive and significant effect on employee job satisfaction.Keywords: competence, quality of work life, workload and employee job satisfaction